2016
DOI: 10.1038/srep22224
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimation of hydraulic conductivity by combining stochastically simulated hydrofacies with geophysical data

Abstract: Hydraulic conductivity is a major parameter affecting the output accuracy of groundwater flow and transport models. The most commonly used semi-empirical formula for estimating conductivity is Kozeny-Carman equation. However, this method alone does not work well with heterogeneous strata. Two important parameters, grain size and porosity, often show spatial variations at different scales. This study proposes a method for estimating conductivity distributions by combining a stochastic hydrofacies model with geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Spatio-temporal dynamics of soil moisture content affects evapotranspiration, deep drainage and local recharge processes. Electrical resistivity is inversely related to soil moisture content and this relationship is largely controlled by soil physico-chemical properties such as texture, particle size and geometry of pores (void distribution and form), and pore fillings 14 , 22 , 28 . The relationship is therefore soil-specific and follows linear or non-linear relationships that can include second order polynomial, power, exponential and logarithmic relationships 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatio-temporal dynamics of soil moisture content affects evapotranspiration, deep drainage and local recharge processes. Electrical resistivity is inversely related to soil moisture content and this relationship is largely controlled by soil physico-chemical properties such as texture, particle size and geometry of pores (void distribution and form), and pore fillings 14 , 22 , 28 . The relationship is therefore soil-specific and follows linear or non-linear relationships that can include second order polynomial, power, exponential and logarithmic relationships 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The vadose zone in water-limited regions is usually thick 19 21 and deep percolation of water and storage in the unsaturated zone is sensitive to the depth of the rooting system 20 . Alteration in water use patterns and rooting architecture 22 associated with changes in vegetation functional type, such as a transition between grassland and woodlands, is likely to affect the deep percolation dynamics and local recharge processes 17 , 23 , 24 . A global synthesis of groundwater recharge showed that grasslands produce higher recharge compared to woodlands 25 .…”
Section: Introductionmentioning
confidence: 99%
“…which is widely accepted to derive the hydraulic conductivity from grain size and porosity (Soupious et al, 2007;Utom et al, 2013;Khalil and Santos, 2013;Zhu et al, 2016b). In Eq.…”
Section: Hydraulic Conductivity Estimates From Geophysical Acquisitionsmentioning
confidence: 99%
“…Geophysical data (such as surface electric resistivity and various logging data) are relatively inexpensive and can provide considerable information for characterizing subsurface heterogeneous properties (Hubbard et al, 2001;Yeh et al, 2002;Dai et al, 2004a;Morin, 2006;Sikandar et al, 2010;Bevington et al, 2016). Electric resistivity data have been proven useful to derive sediment porosity distributions (Niwas and Singhal, 1985;Niwas et al, 2011;Niwas and Celik, 2012;Zhu et al, 2016b). Zhu et al (2016b) simulated the spatial distributions of hydraulic conductivity by combining the interpolated resistivity on the basis of vertical electrical soundings (VESs) and the stochastic simulated facies through the empirical equation, in which the hydraulic conductivity was converted from the porosity data calculated from resistivity measurements and the grain size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation